Contribution des Paradigmes de l’Intelligence Artificielle au Secteur de l’Exploration Pétrolière - Barr Raid, Salah Eddine;  Mida, Mohamed Laid (university of eloued جامعة الوادي, 2023)
رٌضا ذٌ انطهة انعان عهى انطاقح يٌإ تعذ وٌٕ، تٔانران فإ إ رَاج قذس كث شٍ ي انثرش لٔ ضش سٔي نهرخف فٍ ي أصيح انطهة انطإق ي. فٔ قٔر اُ انشا ،ٍْ فإ ذك نُٕ خ إٍ انصخ سٕ انشق حًٍ ذث ذقذيا يهح ظإ إر أ آَ يشذثطح تعذج ذطث قٍاخ ص اُع حٍ يثم ذقذ شٌ انخصائص ان رًعهقح ت قُم انس إئم، ح ثٍ ذ خٕ الا رْ اًو إنى ان سًاي حٍ أن فُار حٌ ان طًهقح. فٔ زْا ان عً ىُ، فإ اَُ قَ وٕ ترحه مٍ انخصائص انث حٌٍُٕ نه إًد راخ ان سًاي حٍ ي خلال انص سٕ ان قًطع حٍ تالأشعح انس حٍٍُ انر ذ ثًم انث ىُ ان كًٍش سٔك تٕ حٍ انذاخه حٍ نهخضا انثرش نٔ ت ذٓف ذط شٌٕ رًَٕج يحاكاج أقع لأداء ان إًد راخ ان سًاي حٍ نهق اٍو تق اٍساخ سق حًٍ عهى ان إًد يثم انشثكح ان سًاي حٍ كٔزنك حدى ان سًاياخ أن شًًاخ، ئ فإ انردضئح انث اُئ حٍ نهص سٕ انصخش حٌ عادج يا ذطثق ظَشا نثساطر آ ح ثٍ عٌرثش كم )ف كٕسم( رٌُ إيا إنى يدال يساي أ صهة. عهى زْا الأساط فإ اَُ اعر ذً اَ انردضئح انث اُئ حٍ أن ثً حٍُ عهى انشثكاخ انعصث حٍ الانرفاف حٍ، ف آ أحذ، سٌهظ ان حُٓ ان قًرشذ انض ءٕ عهى انخصائص انثرش غٔغشاف حٍ نهخضا اَخ كٔزنك كٍْم ان سًاو ي أخم حساب ان عًه اًخ انثرش فٔ ضٍ اٌئ حٍ، ك اً ذعط زْ ان قًاستح ذ إفقا ت رَائح ان سًاي حٍ أن فُار حٌ نلأ سٔاط راخ ان سًايح رَٔائح انرداسب ان خًثش حٌ.Global energy demand is increasing. Therefore, more oil production is essential to mitigate energy demand crisis. Nowadays, digital rock technology shows outstanding advances and is related to several industrial applications such as the estimation of properties relatives to fluid transport where the attention was diverted towards porosity and absolute permeability. In this sens , we analyze the structural fe atures relatives to porous materials through X ray computed tomography images depicting the reservoir oil internal micro structure with the ultimate aim of building realistic simulation model of the porous materials performance to run digital measurements on the porous material like the porous network and the size of pore and throat Indeed, binary rock images segmentation is often applied for its simplicity where each voxel is considered as belonging to pore space or solid we have considered both binary and CNNs b ased segmentation. The proposed approach highlights the reservoirs petrological characteristics along with the structure of pores in order to calculate the petrophysical parameters The proposed approach gives good agreement of both porosity and permeability of porous media with laboratory experiments.
mémoire master informatuque
Keywords: ذص شٌٕ يقطع تالأشعح انس حٍٍُ، صخشج، يسايح، ي شً، ترش لٔ، يساي حٍ، فَار حٌ يطهقح، ذداسب يخثش حٌ، ذدضئح، شثكاخ عصث حٍ ذلاف فٍ حٍ، انرعهى انع قًٍ، ق اُع، رًَٕج "; X ray tomography, rock, porosity, corridor, petroleum, porosity, absolute permeability, laboratory experiments, segmentation, convolutional neural networks, deep learning, mask, U Net model.